Antioxidants and Pregnancy: Impact on Maternal and Fetal Health - *Emmanuel Ifeanyi Obeagu; Getrude Uzoma Obeagu; Joseph Obiezu Chukwujekwu Ezeonwumelu; Esther Ugo Alum; Okechukwu PaulChima Ugwu (NEWPORT INTERNATIONAL JOURNAL OF BIOLOGICAL AND APPLIED SCIENCES, 2023)
Pregnancy represents a physiological state characterized by increased metabolic demands and heightened oxidative stress, posing potential risks to both maternal health and fetal development. Oxidative stress, resulting from an imbalance between reactive oxygen species (ROS) production and antioxidant defense mechanisms, has been implicated in various pregnancy complications such as preeclampsia, gestational diabetes, preterm birth, and fetal developmental abnormalities. Antioxidants, a diverse group of compounds abundant in fruits, vegetables, and certain supplements, play a pivotal role in neutralizing ROS and mitigating oxidative damage. This comprehensive review aims to elucidate the impact of antioxidants on maternal and fetal health during pregnancy. This paper underscores the crucial influence of antioxidants on fetal development. Antioxidants have shown promise in protecting fetal cells and tissues from oxidative damage, potentially reducing the risk of adverse pregnancy outcomes, birth defects, and preterm birth. In conclusion, while antioxidants exhibit potential benefits in mitigating oxidative stress and NEWPORT INTERNATIONAL JOURNAL OF BIOLOGICAL AND APPLIED SCIENCES (NIJBAS) Volume 4 Issue 1 2023 ©NIJBAS Publications 2023 OPEN ACCESS ONLINE ISSN: 2992-5797 PRINT ISSN: 2992-6122 ©Obeagu et al., 2023 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. Page | 18 improving pregnancy outcomes, further research is warranted to elucidate optimal dosages, potential interactions, and long-term implications. This review offers insights into the current understanding of antioxidants in pregnancy and emphasizes their significance in promoting maternal well-being and optimal fetal development. Keywords: Antioxidants, Pregnancy, Maternal and Fetal Health